Gross Morphological and Sex Wise Morphometrical Studies on the Fourth, Fifth and Sixth Thoracic Vertebrae of Blue Bull (Boselaphus tragocamelus) - Sathapathy, Srinivas; Dhote, Balwinder Singh; Mahanta, Dwipjyoti; Tamilselvan, S.; Meena Mrigesh; Joshi, Suman Kumari (International Journal of Livestock Research, 2019)
The present study was carried out on the fourth, fifth and sixth thoracic vertebrae of six specimens of adult Blue bull (Boselaphus tragocamelus) of either sex. The first, second and third thoracic vertebrae were characterized by long supraspinous process, cylindrical, but shorter centrum. The length and breadth of supra spinous processes was observed to decrease from T4 to T6. The transverse process was thick, strong that presented a rounded non-articular mammillary process and a facet ventrally. The costal facets were placed on either side at the end of the articular extremities of the centrum. The cranial articular processes were represented by oval facets on the anterior part of the arch and faced upwards, whereas the caudal ones spring from the base of the dorsal supraspinous process. The biometrical observations on different parameters of fourth, fifth and sixth thoracic vertebrae reflected significance (P<0.05) differences between the sexes of this species.